Optimal power management framework for smart homes using electric vehicles and energy storage. (January 2022) - ur Rehman, Ubaid; Yaqoob, Kamran; Adil Khan, Muhammad
Highlights: This paper proposes a novel home power management system to control household usage. By Mixed Integer Linear Programming charging/discharging of ESU and EV is optimized. A heuristic approach is used to enhance the production of domestic PV power plant. During 24 h most of the time smart home appliances are power by PV, EV and ESU. This system also contributes in the stabilization of smart grid. Abstract: Residential Buildings are considered as the most important and eventual beneficial part of the future smart energy system. Therefore, development of an efficient home power management framework (HPMF) to intelligently manage the prosumers power procurement is necessary. This system will be used to optimally govern the use of home appliances, it will also manage the power generated by renewables (PGR), as well as this system will also optimization the charging/discharging of the energy storage units (ESU) and electric vehicles (EVs). In this paper, we have proposed a holistic method to optimize the use of different home appliances according to the prosumers preferences and defined schedule. Moreover, a separate system for controlling the charging/discharging of ESU and EVs has been designed which considers their capital costs while integrating them with the HPMF to enable flexibility in the use of stored power which enhances the desired economic outcomes besides it also increases the ESU life. Using Mixed integral linear programming' (MILP') and the proposed power management framework it is possible to intelligently optimize the energy procurement of a smart home, which not only guarantee the minimal energy procurement cost as well as it increases consumer comfort. A comprehensive performance analysis of the proposed model has been carried out to prove its robustness and effectiveness.